(untitled) (Research, Society and Development, 2020)
The work aims to present a qualitative survey of the results of the application of the Inquiry Based Teaching-learning Sequence (SEI), named “Why does anyone who lives in the South Pole not fall down? Investigating the Force of Gravit”, in an elementary school class, together with an analysis of the development of the argumentative and investigative process in scientific literacy. We show an experience report together with a qualitative research, as we boast data collected through pedagogical action with students from a fifth grade class in elementary school, in the rural community of São Domingos do Capim, municipality of the state of Pará (Brazil) through analysis filming, audio, observation and written reports, following the form in which they were presented and recorded. From the observed responses, it was evidenced the (re) construction of concepts involving the word FORCE in the students when answering the question of the SEI title. As a result, they understood that any body, being in any part of the terrestrial globe at a Givenchy distance on its surface, is pulled towards the center of the planet and this phenomenon extends to any star in the cosmos.